Construction coefficient in the settlements of Gllogoc Municipality (Republic of Kosova) - Cela, Tomor; Ramadani, Ibrahim (Bulletin of Geography. Socio-economic Series, 2019)
Subject discussed in this paper focuses mainly on the importance of using spatial data for analysis and monitoring of social and economic development in the municipal land surface area, with the purpose of getting results, which will help in making important decisions in regards to the direction of spatial development in the future. Use of land surface must be in full compliance with spatial plans, both at national and local levels. This is the reason why the municipality of Gllogoc has also approved the Municipal Development Plan for the time period 2010 - 2020. In the case of Gllogoc execution of numerous projects in infrastructure, education, culture, sports and other economic and housing buildings have contributed to the rapid transformation of the land surface area. However, lack of political power and will to implement the rules set by development plans still continue to be destructive elements for land surface areas. Over the past decade, namely the period after 1999, there has been considerable increase in construction activities. Although the local plan gives property owners the right to develop and use the property in accordance with their interests, these regulations do not give them the right to work outside the legal provisions of the local plan. As a result of the deficiency of astringent administrative and legal regulations, as well as disregard of urban regulations, settlements of the municipality of Gllogoc continue to further expand land surface areas where construction is performed in a wild manner, without plans and with disturbing effects on the environment and the land surface area. The results obtained in this paper will help in making important decisions to constrain the construction zone, as well as to provide the necessary recommendations for steps to be taken in function of the land use for common interest.